Adapting Trauma-Informed Kickboxing for the Salvadoran Context: A Practitioner Essay - Verry, Georgia (Violence against women, 2025)
This practitioner essay will discuss the evidence base for an Australian trauma-informed kickboxing program, The Fight Back Project. We share key differences and adjustments while delivering this program in the Salvadoran context. We consider practitioner assumptions and limitations when transferring trauma-informed practice principles from the Global North to the Central American setting, and the criticality of gender-responsive adaptations. Drawing from existing research on the benefits of trauma-informed martial arts as a form of physical exercise, we describe the collaborative development and implementation of a trauma-informed kickboxing program alongside a local, community-led organization.